Mandibular Osteitis Fibrosa Cystica as First Sign of Vitamin D Deficiency - Nour Mellouli; Raouaa Belkacem Chebil; Marwa Darej; Yosra Hasni; Lamia Oualha; Nabiha Douki (Case Reports in Dentistry)
Introduction. Brown tumors of hyperparathyroidism are locally destructive bone lesions. They are the late clinical consequence of the disease. They can occur in primary, secondary, and rarely tertiary forms. They affect usually long bones and less frequently those of the maxilla. Case Report. Our 45-year-old female patient presented with a mandibular tumor next to the first right lower molar. At first, we have chosen tooth extraction and tumor excision. When the histological report showed the giant cell tumor we suspected a metabolic bone disorder. Biochemical tests screened hyperparathyroidism and severe vitamin D deficiency, and parathyroid scintiscan revealed parathyroid adenoma. Discussion. The association of hyperparathyroidism and vitamin D deficiency leads to diagnostic uncertainty. First, secondary hyperparathyroidism can be due vitamin D deficiency. Second, data available show that vitamin D deficiency is more prevalent in patients with primary hyperparathyroidism than in general population. Hyperparathyroidism management is based on correct and precise diagnosis. Furthermore, the resolution of brown tumors depends on the cure of hyperparathyroidism. In fact, bone lesions should regress after biological tests’ normalization. Conclusion. Clinicians should be aware of such rare and complicated presentation. They must consider the diagnosis of the brown tumor to avoid extensive surgical excision and teeth extractions.